2015
DOI: 10.1246/cl.150933
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Hysteresis in IV Curves for Planar Structure Perovskite Solar Cells Rationalized with a Surface Boundary-induced Capacitance Model

Abstract: For efficient hybrid solar cells based on organometal halide perovskites, the real origin of the IV hysteresis became a big issue and has been discussed widely. In this study, simulated IV curves of different equivalent circuit models were validated with experimental IV curves of a planar perovskite solar cell with the power conversion efficiency (PCE) of 18.0% and 8.8% on reverse scan (from open circuit to short circuit) and forward scan (from short circuit to open circuit), respectively. We found that an equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
83
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 18 publications
6
83
1
Order By: Relevance
“…[8,[11][12][13] In one of our previous reports,w e also found that the origin of hysteresis in I-V curvesc an be explained by an equivalent-circuit modeli ncluding ac apacitance as ac omponent.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…[8,[11][12][13] In one of our previous reports,w e also found that the origin of hysteresis in I-V curvesc an be explained by an equivalent-circuit modeli ncluding ac apacitance as ac omponent.…”
mentioning
confidence: 66%
“…[1][2][3] The I-V hysteresis creates an ambiguity about the actual power of the devices and persists as ac hallenge in this field. [4][5] To elucidate its origin,s everalh ypothesesi ncluding ion migration/displacement, ferroelectric polarization, trappingo fe lectronsa t the interfaces,a nd capacitive effects [6][7][8] were proposed. Migrationo fi ons such as CH 3 NH 3 + ,I À ,P b 2 + ,a nd H + [9] was also suggested as origin of hysteresis.D iffusion of intrinsic ionic defects in CH 3 NH 3 PbI 3 layer implies ah igh long-term stability and performance of the solar cells.I on migration can create defects in the crystal, and these defects can affect the physical and charge-transfer properties at interfaces, eventually leading to charge accumulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several components are considered for the origin of hysteresis such as ferroelectricity, [10][11][12][13] ion migration, [14][15][16][17][18][19][20][21][22] carrier trapping 15,26 and capacitance component at the interfaces. [27][28][29][30][31][32] The effect of ferroelectricity is analyzed as the response of bias poling. The effect of ion migration and charge trapping is investigated based on the transient photocurrent analysis and device simulation.…”
mentioning
confidence: 99%